The Effect of Sales on Net Profit of Food and Beverage Companies Listed on the Indonesian Stock Exchange - Pratiwi, Dwi Dian; Haliah, Haliah; Nirwana, Nirwana (PT. Riset Press International, 2024)
This research aims to determine the effect of sales on the net profit of food and beverage companies listed on the IDX. The variables of this research are: (1) Sales as the dependent variable (Y) which is measured by sales taken from sales contained in the profit/loss report, and (2) Net Profit as the independent variable (X). The population in this study is the report financial statements of food and beverage companies listed on the Indonesia Stock Exchange, while the sample in this study is the financial reports of food and beverage companies listed on the Indonesia Stock Exchange which published complete annual reports from 2016-2020 and obtained net profits from 2016-2020 which were taken using purposive sampling technique. Data collection was carried out using documentation techniques. Data analysis was carried out using simple linear regression analysis (t test and coefficient of determination test) using SPSS v 25. Based on the results of simple linear regression analysis, the equation Y = 23.556 + 0.046X was obtained, which means that when sales are zero and do not change, the net profit is equal to 23,556 and for every increase in sales (X) by one unit, the net profit variable (Y) will increase by 0.046. The results of the t test show a sig value <0.05 (000<0.05), which means that the hypothesis is accepted that sales have a positive and significant effect on the net profit of food and beverage companies listed on the Indonesia Stock Exchange. The results of the coefficient of determination test (r2) show an r2 value of 0.557 or 55.7%. This means that the magnitude of the influence of the independent variable (sales) on the dependent variable (net profit) is 55.7% while the remaining 44.3% is influenced by other factors outside of this research